The aesthetic imagery of traditional garden door and window forms: a case study of the four major traditional gardens of Lingnan - Wang, Zhongwei; Zheng, Ruyue; Tang, Jian; Wang, Shaobin; He, Xubo (Multidisciplinary Digital Publishing Institute, 2025)
Traditional Lingnan gardens, one of the three major types of Chinese garden design, have evolved over nearly a millennium, embodying the distinctive craftsmanship and aesthetic sensibilities of the Lingnan region. The architectural elements of doors and windows in these gardens serve as key expressions of regional cultural identity. This study focuses on four renowned Lingnan gardens (e.g., Yuyin Garden in Guangzhou, Liang Garden in Foshan, Qinghui Garden in Shunde, and Ke Garden in Dongguan) as primary case studies to examine the typologies, decorative characteristics, and aesthetic qualities of their doors and windows. Based on aesthetic imagery, the research elucidates both the functional and structural principles governing these designs, while also exploring their aesthetic resonance with traditional Chinese arts, such as calligraphy, painting, and poetry. By deepening the theoretical understanding of the formal and artistic features of Lingnan garden doors and windows, this study contributes to advancing the scholarly discourse on traditional garden architecture and supports the ongoing cultural preservation of this important heritage.